Implementation of The Integrated Development Post for Non-Communicable Diseases - Mustajab, Abdullah Azam; Romdiyah (Babali Publisher, 2024)
Introduction: Non-communicable diseases (NCDs/PTM) are the cause of morbidity, disability and death worldwide. NCDs are like stroke, hypertension and diabetes mellitus. NCDs can be prevented and controlled. Therefore, the government created a program to overcome this problem. The program is called Posbindu PTM. Posbindu PTM is a community service as an effort to detect early NCDs as well as follow-up efforts if NCDs are found in community groups. There are many studies on Posbindu PTM. However, there is no research that explains the partnerships carried out in the Posbindu PTM program. Therefore, researchers are interested in examining the phenomenon of Posbindu partnerships in Puskesmas of Mojotengah Work Area, Wonosobo. Objectives: This study is to describe the implementation of Posbindu PTM partnerships in the working area of ​​Mojotengah Puskesmas, Wonosobo. Methods: This research is a descriptive research. In detail, this research used a qualitative descriptive approach. Data were collected by conducting semi-structured interviews. The saturation in this study was obtained from ten participants. Furthermore, researchers in analyzing data used content analysis. Results: Researchers revealed five themes in this study. The five themes include cooperation before the implementation of Posbindu, cooperation in Posbindu activities, the lack of knowledge and skill development activities for cadres, double cadres and support facilities. Conclussion: The partnership between health cadres is very important. In addition, partnerships also function to support the continuity and smooth implementation of NCDs Posbindu activities in the region. Cooperation with private parties such as clinics, independent practice of health workers, companies or factories has not been implemented.